Effect of sugar supplementation in lactating dairy cows - Vargas Rodriguez, Claudio Fabian (Kansas State University, 2012)
During the past decades, the dairy industry has been challenged to find alternative approaches in order to feed cows without affecting their performance or increasing production costs. To accomplish these objectives, some options that have been implemented are the inclusion of short chain carbohydrates to replace starch and the addition of synthetic supplements to increase feed efficiency. In order to assess the impact of these strategies, an experiment was conducted to evaluate productive responses of lactating dairy cattle when they received sucrose and/or exogenous amylase in low starch diets. The results indicated that milk production, milk component profile, and feed efficiency were not significantly altered by the use of the enzyme, sucrose inclusion, or the combination of both. Comparing these results with the literature revealed apparent inconsistencies in responses to the inclusion of sugar in dairy rations. For that reason, a meta-analysis was performed to determine the impact of different sugar sources on milk production, and also to evaluate the impact of other dietary factors on response to dietary sugar. The results indicated that dry matter intake responses were significantly (P < 0.05) affected by an interaction between added sugar and dietary forage neutral detergent fiber content, but overall, dry matter intake tended to increase when sugar replaced corn grain in diets. Energy corrected milk was not affected by dietary sugar, but milk production showed a tendency to respond to treatment, dependent on an interaction between added sugar and rumen undegradable protein. In summary, sugar inclusion may promote small increases in dry matter intake, but the impact on milk production is inconsistent; both factors may be influenced by the diet to which sugar is added.
Keywords: Sugar supplementation; Milk production; Energy; Sucrose; Molasses; Animal Sciences (0475)